Status of nosocomial tuberculosis transmission prevention in hospitals in Thailand - Unahalekhaka A. (2014)
A national survey was conducted during July to September 2009 to determine tuberculosis (TB) prevention activities, problems, and support needed of Thai hospitals. Ninety-seven percent of hospitals established TB isolation policy, 96.3% provided guidelines for caring of TB patients, 95% and 91.8% provided prevention of TB transmission and environmental management guideline, and 92.6% established screening system for TB in the outpatient department (OPD). A half of hospitals had problems with isolation rooms and difficulties in screening TB cases in the OPD. Support needed included consultation on structure and ventilation systems, personnel training, national TB prevention, and TB screening guideline. Strengthening TB prevention activities, providing expert consultation, and national guidelines may help hospitals improve their TB prevention activities. Copyright © 2014 Published by Elsevier Inc.